Prolonged Unconsciousness and Delirium with Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The incidence and duration of unconsciousness and delirious behavior in children with febrile seizures were studied at Nagoya University Graduate School of Medicine and other centers in Japan.